Influence of Bradyrhizobium japonicum UKM V-6035 inoculation on the soybean photosynthetic apparatus - Adamchuk-Chala, N. I.; Yacenko, V. A.; Iutynska, G. O. (Reports of the National Academy of Sciences of Ukraine, 2014)
The architectonics of microcenosis of field-grown transgenic soybean plants inoculated by nodule bacteria with parallel monitoring of the morphology and the functional organization of a plant photosynthetic apparatus by methods of electron microscopy and remote spectrophotometry is investigated. The increase of the bacteria number on the surface of main root and rhizosphere is determined in inoculated soybean plants. The palisade mesophyll morphometric investigation has confirmed the statistically essential increase of the mesophyll width the area of mesophyll cells, coefficient of palisade, coefficient of plasticity, and a part of cloroplasts in the summary mesophyll are in comparison with those of uninoculated plants. Morphological changes in photomembrane development are confirmed in spectrophotometrical estimations of main pigments in a leaf blade.